Familiness and Innovation: Resource Bundling as the Missing Link - Carnes, Christina Matz; Ireland, R. Duane (Entrepreneurship Theory and Practice, 2013)
Using resource–based logic, we integrate and extend theory and research on familiness and innovation in family firms. Supporting our efforts to do this is the suggestion that recent mixed results regarding the ability of family firms to innovate are at least partially accounted for by the failure to fully consider the importance of resource bundling processes as a mediator of the relationship between familiness as a unique organizational resource and innovation. Specifically, we suggest that the individual components of the resource bundling process—stabilizing, enriching, and pioneering—each mediate the relationship between familiness and innovation, and that these mediation effects account for at least part of the previously reported inconsistent results. Using theory and by integrating insights about familiness, innovation, and resource bundling, we seek to provide a more complete model of conditions affecting family firms’ ability to innovate.